ENHANCING VALUE OF CUSTOMARY LAND: A CASE STUDY OF NEGERI SEMBILAN - Jaria Maidin, Ainul; Zulkarnain, Ramawansyah; Sulaiman, Siti Sarah; Ramli, Norhidayah Mohd (Jurnal Media Hukum, 2013)
This paper examines the role of law in enhancing the value of customary land which is an integral part of the social and economic aspect of the adat perpatih community in the State of Negeri Sembilan, Malaysia. Tracts of customary land has been left idle for some time since 1980s mainly because of the wrong perception that agricultural activities will not yield fast and high returns. The Malaysian government identified various strategies to help alleviate rural poverty since the early days of independence. Despite the efforts undertaken by the government, the major problem posed to the government agencies is the increasing rate of idle agricultural land. Data were collected from interviews with affected landowners in Negeri Sembilan, the adat leaders, the State Authorities responsible for land administration and development, Federal government agencies established to address rural development strategies to identify the reasons for the increase in the idle agricultural land despite the policies and measures undertaken by the government for promoting efficient use of the land. Research identified that there are factors impacting adversely on the successful implementation of the governmentâs plans to develop idle agricultural lands. This problem if left not being watched will impact on the supply of agriculture land available for development. This paper sets out the legal measures that can be adopted in addressing issues relating to idle agricultural land, the problems faced and the proposals to overcome the problems to prevent the loss of supply of land available for agriculture development which is very crucial to ensure food security and promote sustainable development of the rural community that can have the effect of enhancing the values of customary land.Key words: law for development of land, sustainable development of rural land